2020
DOI: 10.1158/0008-5472.can-19-3717
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Spread of Ovarian Cancer Harbors Therapeutic Vulnerabilities Regulated by FOXM1 and EGFR/ERBB2 Signaling

Abstract: Peritoneal spread is the primary mechanism of metastasis of ovarian cancer, and survival of ovarian cancer cells in the peritoneal cavity as nonadherent spheroids and their adherence to the mesothelium of distant organs lead to cancer progression, metastasis, and mortality. However, the mechanisms that govern this metastatic process in ovarian cancer cells remain poorly understood. In this study, we cultured ovarian cancer cell lines in adherent and nonadherent conditions in vitro and analyzed changes in mRNA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…FOXM1 and RHNO1 are co-expressed as a result of co-regulation by the F/R-BDP and are overexpressed in HGSC and numerous other cancers ( Barger et al, 2019 ; this study). The oncogenic functions of FOXM1 in HGSC include cell cycle progression, genomic instability, tumor invasion, and metastatic spread ( Parashar et al, 2020 ; Barger et al, 2019 ; Barger et al, 2015 ). On the other hand, RHNO1 may promote oncogenesis by increasing the efficiency of the ATR-Chk1-dependent RS response, which protects cells from excessive DNA damage and promotes cell survival ( Kim et al, 2010 ; Cotta-Ramusino et al, 2011 ; Lindsey-Boltz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FOXM1 and RHNO1 are co-expressed as a result of co-regulation by the F/R-BDP and are overexpressed in HGSC and numerous other cancers ( Barger et al, 2019 ; this study). The oncogenic functions of FOXM1 in HGSC include cell cycle progression, genomic instability, tumor invasion, and metastatic spread ( Parashar et al, 2020 ; Barger et al, 2019 ; Barger et al, 2015 ). On the other hand, RHNO1 may promote oncogenesis by increasing the efficiency of the ATR-Chk1-dependent RS response, which protects cells from excessive DNA damage and promotes cell survival ( Kim et al, 2010 ; Cotta-Ramusino et al, 2011 ; Lindsey-Boltz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The forkhead/winged helix domain transcription factor FOXM1 promotes cancer by transactivating genes with oncogenic potential ( Halasi and Gartel, 2013a ; Kalathil et al, 2020 ). Cell phenotypes promoted by FOXM1 include cell cycle transitions ( Costa, 2005 ; Laoukili et al, 2005 ; Wonsey and Follettie, 2005 ), DNA repair ( Maachani et al, 2016 ; Park et al, 2012 ; Monteiro et al, 2013 ; Khongkow et al, 2014 ; Roh et al, 2020 ), cell invasion and metastasis ( Wang et al, 2020 ; Luo et al, 2018 ; Mao et al, 2019 ; Parashar et al, 2020 ), and chemoresistance ( Roh et al, 2020 ; Fang et al, 2018 ; Tassi et al, 2017 ; Kwok et al, 2010 ; Carr et al, 2010 ; Zhao et al, 2014 ). Pan-cancer analyses have revealed that FOXM1 overexpression is widespread in human cancer and is linked to reduced patient survival and genomic instability ( Jiang et al, 2015 ; Li et al, 2017a ; Barger et al, 2019 ; Gentles et al, 2015 ; Carter et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovarian cancer, FOXM1 also induces the expression of integrins and matrix proteins: ITGB1 [ 231 ], ITGAV [ 231 ], ITGA5 [ 231 ], LMNB1 [ 231 ], and FN1 [ 231 ], which may facilitate adhesion of ovarian cancer cells to new organs. In keratinocytes, ectopic overexpression of FOXM1 in combination with the loss of TP53 enhanced integrin β1 expression [ 145 ].…”
Section: Foxm1 Oncogenic Functionsmentioning
confidence: 99%
“…Globally, a total of 21,750 new cases are diagnosed as ovarian cancer each year, with 13,940 cancer-specific deaths [ 1 3 ]. Notably, peritoneal spread was reported as the primary metastasis in ovarian cancer [ 4 ], in which malignant cells circulated in the peritoneal fluid to produce the later spread in abdominal organs [ 5 ]. The previous study reported that the cancer stem cell-like properties play a positive role in metastatic spread [ 6 ].…”
Section: Introductionmentioning
confidence: 99%